(untitled) (The Journal of Psychology and Sociology, 2014)
Article is devoted to the concept of «deviant behavior» of foreign and domestic scientists. Analyzing the interdisciplinary feature of deviant behavior, the author gives examples of classification (sociological, psychological, educational, legal) of a number of famous explorers of our time. When writing an article explored and used as works of Russian scientists and local researchers to this problem.